Concentration and Horizontal Integration in Milk Production - Horváth, József (Acta Agraria Debreceniensis, 2004)
Agriculture in Hungary was characterised by the duality of large-scale farms (co-ops and state farms) and small-scale private enterprises until the beginning of the 1990s. Due to the privatisation and transformation of co-ops farm structure has significantly changed. The transformation of the structure is not considered to be a completed process. Level of concentration and integration on private farms are rising, new co-operation forms are appearing and new types of enterprises and producers’ groups are being formed.Concentration and integration have great importance in the dairy sector among agricultural enterprises. In recent years, milk production in the European Union has been characterised by concentration, leading to greater competitiveness. Today, most dairy producers belong to different kinds of producers’ organisations as concentrated demand may only be competitive by meeting concentrated supply. In Hungary, the problems of production have been the fragmentation and decrease of the average farm size while, at the same time, concentration has occurred in the processing sector. Establishing producers’ groups may be one of the solutions for improving competitiveness production.